Appraising fiscal reaction functions - Afonso, António (2012)
We estimate fiscal responses for an OECD panel, accounting for cross-country interactions, and also estimate the fiscal responses in a panel VAR. We find that governments have increased primary balances when facing higher government indebtedness, implying a Ricardian fiscal regime, while primary balances have improved to reduce government debt. These results hold for the single regression panel analysis and for the panel VAR.